2019
DOI: 10.1177/0739456x19861144
|View full text |Cite
|
Sign up to set email alerts
|

Plans that Disrupt Development: Equity Policies and Social Vulnerability in Six Coastal Cities

Abstract: Urban plans often ignore the uneven impacts of hazards on socially vulnerable populations. We evaluate the degree to which equity policies in local networks of plans support risk reduction for socially vulnerable populations, and examine the relationship between equity policies scores and the level of social vulnerability in six cities exposed to floods and projected sea level rise. We find high variability in equity policy support for risk reduction, and that equity policies in plans actually actively increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 57 publications
0
50
1
Order By: Relevance
“…In the past few decades, there have been incoherent definitions, interpretations, and analytical models proposed to understand, apply, and assess the notion of resilience and its related concepts (Béné et al, 2018; Berke, Malecha, & Cooper, 2019; Chuang et al, 2018; Pizzo, 2015). The majority of such efforts focus on quantifying indicators to technically guide practitioners and policymakers to achieve resilience as a goal, paying insufficient attention to the complexity, informality, and unpredictability of social dynamics; these linear quantitative approaches also fail to explore the core value of resilience, including justice and inclusiveness (Fainstein, 2018; Weichselgartner & Kelman, 2015; Wisner, 2016).…”
Section: Another Buzzword or The New Insight?mentioning
confidence: 99%
“…In the past few decades, there have been incoherent definitions, interpretations, and analytical models proposed to understand, apply, and assess the notion of resilience and its related concepts (Béné et al, 2018; Berke, Malecha, & Cooper, 2019; Chuang et al, 2018; Pizzo, 2015). The majority of such efforts focus on quantifying indicators to technically guide practitioners and policymakers to achieve resilience as a goal, paying insufficient attention to the complexity, informality, and unpredictability of social dynamics; these linear quantitative approaches also fail to explore the core value of resilience, including justice and inclusiveness (Fainstein, 2018; Weichselgartner & Kelman, 2015; Wisner, 2016).…”
Section: Another Buzzword or The New Insight?mentioning
confidence: 99%
“…Through revealing fundamental design principles with implications for actions, our research can also improve the nation's flood resilience, in support of science-based measures for accessible, affordable, and universal design interventions. More comprehensive knowledge of how cross-scale resilience design criteria influence adaptive behavior can inform more effective approaches as planning practitioners reevaluate their community network of plans (Berke et al, 2019;Yu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, policy development largely fails to prioritize actions that are critical and consistent in reducing risk for vulnerable populations [24]. According to Berke et al [78], multiple groups may create plans to pursue their interests, resulting in a fragmented network of plans that are poorly coordinated, which could potentially conflict with each other and, subsequently, increase urban risks. As mentioned in [106], a governance dilemma can exist where subordinate governing bodies are unwilling to support policy developed by the higher level of government, creating a significant obstacle to implementing a collective approach to risk-sensitive urban development.…”
Section: Governancementioning
confidence: 99%
“…As mentioned in [106], a governance dilemma can exist where subordinate governing bodies are unwilling to support policy developed by the higher level of government, creating a significant obstacle to implementing a collective approach to risk-sensitive urban development. In [78], Berke et al suggest that one of the reasons for such unwillingness by the subordinate governing bodies to support policies is due to the inability of the higher-level government bodies to create equity policies that support risk reduction for vulnerable communities in their local context. It can be observed that cities tend to adopt climate policies and hazard mitigation plans or implement strategies that are being developed at the national level, with limited engagement at the local level [94,107].…”
Section: Governancementioning
confidence: 99%
See 1 more Smart Citation